Hydrogeochemical Characteristics and Geothermometry of Hot Springs in the Tensile Tectonic Region Leizhou Peninsula and Hainan Island in South China. (17th March 2022) - Hu, Hongyu; Lu, Guoping; Lu, Qiuying; Li, Yan; Xie, Linjun; Lin, Xuanhao; Wu, Ming; Mo, Cehui; Zhang, Bei
Abstract : Hydrochemistry and isotopes are studied for characterizations of geothermal waters, groundwaters, and surface waters in Leizhou Peninsula (LZ) and the northern part of Hainan Island (HN) across the tensile-tectonic Qiongzhou Strait, southern China. Water chemistry results showed that most geothermal waters are of alkaline and HCO3 -Na types, while shallow groundwater samples were significantly different with HCO3 -Ca, HCO3 -Mg, and HNO3 -Ca types. Stable isotope data indicated that the source of LZ geothermal waters is of atmospheric precipitation, while HN geothermal water has a slight "oxygen drift". Cation geothermometers and silica geothermometers could appropriately predict reservoir temperatures. Based on multicomponent mineral equilibria and quart geothermometer without steam loss, reservoir temperatures were estimated to be in the range of 65.0°C to 165.0°C at an average circulation depth of 2023 m, substantiated with data from a thousand-meter-depth borehole. The saturation indexes (SI) simulated by PHREEQC and Na-K-Mg triangle diagram revealed that the chemical components in the geothermal waters are possibly derived from water-rock interactions at high temperatures. Four simulation paths were established to calculate the mass flux of minerals by PHREEQC program. The hydrothermal circulation process of the volcanic rocks on both sides of the Qiongzhou Strait was similar, but the water-mineral reactions of Leizhou Peninsula were more intense. During the high-temperature hydrothermal deep circulation in the central part of Hainan Island, the molar transfer was low and the degree of mineral reaction is weak. Finally, the geothermal genetic mechanism for the study area of the extensional geostructure was proposed. The findings mark the characteristics for the tensile-tectonic region in slight "oxygen shift", low values of 87 Sr/ 86 Sr for possible deep source from the mantle, and higher reservoir temperatures at shallower circulation depths.